Assessment of inotropic and vasodilating effects of milrinone lactate in patients with dilated cardiomyopathy and severe heart failure - Bregagnollo, Edson Antônio [UNESP]; Fortes, Adjair Humberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 1999)
OBJECTIVE: To assess the hemodynamic and vasodilating effects of milrinone lactate (ML) in patients with dilated cardiomyopathy (DCM) and New York Heart Association (NYHA) class III and IV heart failure. METHODS: Twenty patients with DCM and NYHA class III and IV heart failure were studied. The hemodynamic and vasodilating effects of ML, administered intravenously, were evaluated. The following variables were compared before and during drug infusion: cardiac output (CO) and cardiac index (CI); pulmonary capillary wedge pressure (PCWP); mean aortic pressure (MAP); mean pulmonary artery pressure (MPAP); mean right atrial pressure (MRAP); left ventricular systolic and end-diastolic pressures (LVSP and LVEDP, respectively); peak rate of left ventricular pressure rise (dP/dt); systemic vascular resistance (SVR); pulmonary vascular resistance (PVR); and heart rate (HR). RESULTS: All patients showed a significant improvement of the analysed parameters of cardiac performance with an increase of CO and CI; a significant improvement in myocardial contractility (dP/dt) and reduction of the LVEDP; PCWP; PAP; MAP; MRAP; SVR; PVR. Were observed no significant increase in HR occurred. CONCLUSION: Milrinone lactate is an inotropic dilating drug that, when administered intravenously, has beneficial effects on cardiac performance and myocardial contractility. It also promotes reduction of SVR and PVR in patients with DCM and NYHA class III and IV of heart failure.
Keywords: heart failure; inotropic agents; milrinone